The Great Migration: Understanding the Cloud Revolution in IT - Mohit Mittal, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This comprehensive article explores the transformative journey of cloud migration in the modern IT landscape, examining its driving forces, benefits, challenges, and critical success factors. The article delves into how organizations across sectors increasingly adopt cloud technologies to enhance operational efficiency, reduce costs, and gain competitive advantages. It highlights the impact on healthcare organizations and discusses the strategic considerations necessary for successful migration. The article examines various aspects of cloud adoption, including financial implications, security concerns, technical challenges, and the importance of proper planning and execution. Through detailed analysis of market trends and industry research, this article provides insights into the current state of cloud computing adoption and its future trajectory while offering guidance for organizations contemplating or undertaking cloud migration initiatives.
Keywords: Cloud Migration; Digital Transformation; Cloud Computing Market; Cloud Security; Cloud Adoption Strategy